2016
DOI: 10.1080/19322909.2015.1124740
|View full text |Cite
|
Sign up to set email alerts
|

The Perfect Storm: Examining User Experience and Conducting a Usability Test to Investigate a Disruptive Academic Library Web Site Redevelopment

Abstract: The researchers conducted a task-based usability test of the effectiveness of online research beginning on the library Web site homepage. The participants included five university faculty members, six graduate students, and six undergraduate students. All participants reported feeling satisfied with their overall research experience, though most were unable to effectively complete all the research tasks of the test. The researchers identified weaknesses in the approach and process of many participants, and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Novice users should be provided with web forms that allow them to communicate with library staff (Pant, 2015, p. 903). Users should be able to differentiate between different resources (Chase et al , 2016, p. 36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novice users should be provided with web forms that allow them to communicate with library staff (Pant, 2015, p. 903). Users should be able to differentiate between different resources (Chase et al , 2016, p. 36).…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of library websites has attracted a large amount of attention from researchers in the field of library and information sciences (Chase et al , 2016; Pant, 2015; Silvis, 2017; Wu and Brown, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A prominent theme arising was that the decision to teach them depended on certain factors. One of these was related to student status – librarians were more inclined to introduce the tool to undergraduates, primarily freshmen or sophomores, because it offered them easy access to research information, especially because they were often unaccustomed to using databases (Buck and Steffy, 2013; Chase, et al , 2016; Dyas-Correia et al , 2015). However, there was still concern as to the volume of information returned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there was still concern as to the volume of information returned. Chase et al (2016, p. 38) found that undergraduates had difficulties with one-box searches because they did not understand the differences between “library search and non-library interfaces and the resources and information these interfaces access”. Once students reached junior, senior or graduate status with more classes concentrating on particular disciplines, some librarians tended to instruct them on subject-specific databases (Dyas-Correia et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Questionnaires are the most widely used method for evaluating websites [5][6][7][8][9][10][11]. These can be administered remotely or in person [12] and used stand-alone or in combination with other methodology, such as observed browsing and interviews following completion of task scenarios [13,14]. Allison et al [7] incorporated methods and attributes from 69 studies to suggest a simple but comprehensive guide to evaluating websites, coined GoodWeb, which follows 4 basic steps:…”
Section: Introduction Backgroundmentioning
confidence: 99%